2016
DOI: 10.1111/aogs.12952
|View full text |Cite
|
Sign up to set email alerts
|

Vacuum extraction in fetal macrosomia and risk of neonatal complications: a population‐based cohort study

Abstract: Vacuum extraction is a risk factor for serious neonatal complications, in particular when used in macrosomic fetuses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
5

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(42 citation statements)
references
References 31 publications
1
36
0
5
Order By: Relevance
“…Although it is beyond the scope of this review to identify the underlying cause of the reduced instrumental delivery, macrosomia has been identified as a risk factor for the use of forceps or vacuum extraction 112. Previous work has identified that prenatal exercise reduces the odds of fetal macrosomia by 31%,113 and as a result, may reduce the risk for instrumental delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Although it is beyond the scope of this review to identify the underlying cause of the reduced instrumental delivery, macrosomia has been identified as a risk factor for the use of forceps or vacuum extraction 112. Previous work has identified that prenatal exercise reduces the odds of fetal macrosomia by 31%,113 and as a result, may reduce the risk for instrumental delivery.…”
Section: Discussionmentioning
confidence: 99%
“…Third, the criteria by which the women underwent one or another type of instrumentation (vacuum or forceps) was based on the obstetricians' experience and skill [50][51][52] (only five obstetricians participated in our study). First, only Malmström vacuum and Kielland forceps were used for the deliveries; therefore, the results obtained should not be generalized to all types of instrumental deliveries.…”
Section: Malmström Vacuum and Kielland Forceps Deliveriesmentioning
confidence: 99%
“…Second, the characteristics of the instrumentation included in our study, such as the station and fetal head position, were limited, and other factors, such as rotation or no rotation of the fetal head, should be evaluated in future studies. Third, the criteria by which the women underwent one or another type of instrumentation (vacuum or forceps) was based on the obstetricians' experience and skill [50][51][52] (only five obstetricians participated in our study). The experience of our obstetricians could have influenced our final results.…”
Section: Ta B L E 3 Levator Ani Muscle Injury and General Levator Hiamentioning
confidence: 99%
“…We thank Dr. McQuivey for his comments (1) and interest in our work (2). Dr. McQuivey's point that the Swedish Medical Birth Register lacks detailed information is well-taken and causal relations among vacuum extraction, birthweight and neonatal complications are difficult to prove using our study design.…”
Section: Sirmentioning
confidence: 99%